An Evaluation on Acoustic Behavior of Untreated Tree Trunks Depending on Bark Physical Properties and Fiber Cell Structure - (:unkn) unknown (TAYLOR & FRANCIS INC, 2022)
In recent years, noise pollution generated by increasing global urbanization has become an important issue. This study focused on determining the sound absorption coefficients (SACs) of untreated tree trunks as natural fiber-based materials and predicting their noise reduction coefficients (NRCs). It also evaluated the effects of noise reduction using numerical data. One of the most effective acoustic characteristics is the normal incidence SAC; this was obtained for trunks belonging to species of black locust, narrow-leafed ash, stone pine, silver lime, sweet chestnut, sessile oak, maritime pine, cedar, and plane in the frequency range of 50-6000 Hz using an impedance tube based on a two-microphone transfer function method. The absorbance of sound was found to correlate with the tree species, trunk diameter, bark shape, and the bark's fibrous structure. The results confirmed that when compared with deciduous species, the trunks of coniferous species exhibit higher NRC values which were recorded as 0.302 +/- 0.005 for stone pine and 0.233 +/- 0.004 for cedar. Furthermore, the surface morphology of the outer bark of different tree species obtained via scanning electron microscopy revealed that significant variations exist in the microstructure of the bark's fiber cells.
Keywords: Untreated tree trunks; natural fiber-based material; sound absorption; impedance tube; bark morphology; noise reduction; TRAFFIC NOISE ATTENUATION; SOUND-ABSORPTION; PROPAGATION; BELTS